2022
DOI: 10.1038/s41598-022-24128-2
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of roadway deformation and failure under different degrees of dynamic disturbance

Abstract: Deformation and failure of the roadway surrounding rock under dynamic disturbance were explored, which is essential for the control of the surrounding rock. The impact of dynamic disturbance on the deformation and failure of the roadway surrounding rock was studied from a single factor perspective using numerical simulation software. The disturbance intensity, frequency, and time were determined to affect the deformation and plastic zone of the surrounding rock. Firstly, a multi-factor integrated study was ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…According to Equations ( 8) and (10), the radial displacement of the road caused by the different degrees of the attenuation stress wave is: The total displacement potential function of the roadway-surrounding rock under P-wave disturbance is as follows [34]:…”
Section: Dynamic Response Of Rock Mass Surrounding the Roadway Under ...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Equations ( 8) and (10), the radial displacement of the road caused by the different degrees of the attenuation stress wave is: The total displacement potential function of the roadway-surrounding rock under P-wave disturbance is as follows [34]:…”
Section: Dynamic Response Of Rock Mass Surrounding the Roadway Under ...mentioning
confidence: 99%
“…The dependence between wave velocity and stress in elastic and non-elastic stage was studied in the paper [9]. Jia et al [10] conducted FLAC3D simulations to analyze roadway deformation and failure under different dynamic disturbances and how significantly dynamic stress influences roof deformation. Han et al [11] studied the dynamic fracture behavior of rock materials and found that increasing dynamic load will promote crack initiation and propagation.…”
Section: Introductionmentioning
confidence: 99%